Method for increasing the permeability of the plasma membrane of a cell and structures suitable for use in such a method - Patents.com
By embedding particles that can absorb electromagnetic radiation into the structure and using laser radiation to cause thermal effects, the challenge of improving cell membrane transparency in the prior art is solved, and efficient and safe increase in cell membrane transparency is achieved, and suitable for large-scale cell engineering applications.
Patent Information
- Application Number
- JP2022517857
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-23
- Filing Date
- 2020-09-21
- Publication Date
- 2025-05-01
- Estimated Expiration
- 2040-09-21
AI Technical Summary
The prior art presents several challenges in improving cell membrane transparency, including the possible toxicity problems caused by direct contact with cells and nanoparticles, as well as the inefficiency and inexplicable limitations of the system.
By embedding particles that can absorb electromagnetic radiation into the structure and placing cells into or near the structure, laser radiation causes thermal effects to increase the transparency of the cell membrane without directly exposing the cells to the particles.
The efficiency of improving cell membrane transparency is achieved, particle release and cytotoxicity problems are avoided, and the method is reusable and suitable for large-scale cell engineering applications.
Smart Images

Figure 0007671282000006 
Figure 0007671282000007 
Figure 0007671282000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for increasing the permeability of the plasma membrane of a cell by introducing the cell onto or near a structure containing embedded particles and irradiating the structure. The method according to the invention does not require contact between the particles and the cell. The present invention further relates to a structure suitable for the method of increasing the permeability of the plasma membrane of a cell. [Background technology]
[0002] The intracellular delivery of exogenous compounds into cells is a common requirement in many biotechnological and biomedical applications. Examples are the generation of mutant cell lines for basic research, drug screening of biopharmaceutical compounds, and the production of cells (e.g. CAR-T cells) for cell-based immunotherapy. Regardless of the specific application, a common challenge is overcoming the cell membrane, which represents a major obstacle especially for macromolecules such as DNA, RNA, and proteins. In recent years, the field has seen a significant increase in research on new physical transfection methods that should be as efficient as possible to deliver molecules, especially macromolecules, while minimizing cytotoxicity.
[0003] Physical methods for delivering compounds into cells have attracted considerable interest. Such methods have in common that they increase the permeability of the cell membrane, allowing the compound to pass through the cell membrane.
[0004] Nanoparticle (NPs) sensitized photoporation is a promising physical method for delivering compounds into cells. In photoporation, cell membranes are temporarily made permeable by a combination of laser irradiation and photoresponsive nanoparticles. Cells are first incubated with nanoparticles, usually gold, iron oxide, or carbon particles, that can adsorb to the cell membrane. Laser irradiation is then applied so that the cell membrane becomes permeable by photothermal or photochemical effects such as localized heating, induction of pressure waves, or generation of reactive oxygen species.
[0005] Although photoporation is a promising technique for producing engineered cells, for example for cell therapy, there are general safety concerns about bringing nanoparticles into contact with cells. Indeed, there is considerable uncertainty about the potential toxicological effects of nanoparticles in general. Furthermore, plasmonic nanoparticles, such as gold nanoparticles, tend to fragment into smaller pieces upon the intense laser illumination used in photoporation. Reportedly, nanometer-sized gold particles can be genotoxic when taken up into cells. Considering that photoporation requires close contact between plasmonic nanoparticles and cells, the use of photoporation to transfect cells, for example for use in cell therapy, may raise nanotoxicity concerns.
[0006] Therefore, it is of current interest to develop methods that avoid direct contact of plasmonic nanoparticles with cells during photoporation.
[0007] US9,957,476 describes a system for cell poration using plasmonic nanoparticles. The system uses a laser to create an optical trap to position the nanoparticles close to the cell, and a laser directed at the optically trapped particle to cause laser-induced destruction of the optically trapped particle, thereby causing cell poration. However, the throughput of the system is limited and cannot be scaled up to process a significant number of cells. As a result, the system is not suitable for the production of large numbers of engineered cells for cell therapy.
[0008] US9,139,416 describes a microfluidic device that includes a substrate with a microchannel with nanowires on the walls of the microchannel. Cells can be photoporated by irradiating them with laser light while they flow through the channel. However, the device does not allow for adjustment of the distance between the plasmonic structure and the cells, which creates the need to maximize the performance of the system, especially when dealing with different cell types. Furthermore, the device suffers from damage to the nanowires, resulting in a limited useful life.
[0009] EP2272945 describes a method for perforating cells by placing them on or near the surface of a substrate provided with a surface structure coated with a thin metal layer, such as a layer of gold, and irradiating the surface of the substrate with a laser pulse. Such a method has the disadvantage that the cell membrane is permeable on one side, i.e. the side where the cell is in contact with the surface structure of the substrate (the underside of the cell), while the compounds that need to be delivered into the cell are mainly present on the opposite side (the upper side of the cell). This limits the efficiency with which molecules can enter the cell, especially large molecules. Summary of the Invention [Problem to be solved by the invention]
[0010] It is an object of the present invention to provide a method for increasing the permeability of the plasma membrane of a cell, which avoids the drawbacks of the methods known in the art.
[0011] Another object of the present invention is to provide a method for increasing the permeability of cells by photothermal processes, in particular by irradiation with electromagnetic radiation, such as laser radiation.
[0012] Another object of the present invention is to provide a method of using a structure comprising particles embedded within the structure to increase the permeability of the plasma membrane of a cell by introducing the cell onto or near the structure and irradiating the structure with electromagnetic radiation.
[0013] It is a further object of the present invention to provide a method for increasing the permeability of cells, in which direct exposure of cells to particles, such as nanoparticles or components thereof, is limited or even avoided.
[0014] It is a further object of the present invention to provide a method for increasing the permeability of cells by using pulsed laser radiation, such as nanosecond pulsed radiation.
[0015] A further object of the present invention is to provide a method for increasing the permeability of cells with enhanced efficiency for the intracellular delivery of cell-impermeable substances, particularly for the intracellular delivery of macromolecules.
[0016] It is also an object to provide a structure comprising particles capable of absorbing electromagnetic radiation, such as nanoparticles, to increase the permeability of the plasma membrane of a cell, wherein the particles and their components are largely, and preferably completely, retained within the structure upon laser activation.
[0017] It is a further object to provide a method for increasing the permeability of cells suitable for use in drug screening, cell therapy, immunotherapy, gene therapy, cell labeling, and the production of engineered cells.
[0018] It is an object of the present invention to provide a structure suitable for use in photothermal processes, which permeabilizes cells introduced onto or near the structure.
[0019] It is a further object of the present invention to provide a structure that can be activated multiple times by laser irradiation to repeatedly increase the permeability of cells. [Means for solving the problem]
[0020] According to a first aspect of the present invention there is provided a method of increasing the permeability of the plasma membrane of a cell, the method comprising: The method includes providing a structure comprising a material and particles capable of absorbing electromagnetic radiation, wherein the particles have a mean equivalent spherical diameter d and are embedded in the material. The structure defines a volume V and a free area surface S. The particles are present in the structure at a concentration in the range of 0.001% to 20% by volume (volume particles / volume structure). At least P percent of the particles present in the structure are embedded in the material such that the shortest distance L between this P percent of particles and said free area surface S of the structure is in the range of 1 nm to 500 nm, and P is at least 60 percent. The method also includes the step of introducing at least one cell onto or near said structure, preferably at a distance of less than 100 μm from said structure. The method also includes irradiating the structure with electromagnetic radiation.
[0021] When the structure is irradiated with electromagnetic radiation, the particles present in the structure, i.e. embedded in the structure, produce a photothermal effect, which causes local and temporary heating of the structure and the free area surface S of the structure. The photothermal effect causes, in particular, local and temporary heating of the material in the vicinity of the irradiated particles. As a result, the temperature of the free area surface in the vicinity of the particles increases. The local and temporary heating induced upon irradiation can result in permeabilization or perforation of membranes or barriers in contact with or in the vicinity of the structure, for example the plasma membrane of cells.
[0022] The temperature of the free area surface S closest to the particle reaches, for example, a temperature at least 10° C. higher than its initial temperature, for example at least 20° C. or at least 30° C. higher than its initial temperature, which is at least 1 nm. 2 It is clear that the temperature rise at the free area surface S closest to the particle can be higher, for example, for at least 1 nm 2 The temperature may be at least 50° C. or at least 100° C. higher than the initial temperature for at least 1 ns for an area of
[0023] The temperature of the free area surface S closest to the particle may reach, for example, a temperature of 60° C., a temperature at which the cell membrane is believed to become permeable. As a result, cells in contact or in close proximity to the locally heated region of the structure, i.e. in contact or in close proximity to the free area surface closest to the irradiated particle, become permeable. It is clear that the temperature of the free area surface S closest to the particle may reach a temperature higher than 60° C., for example, above 100° C.
[0024] The method according to the invention makes it possible to increase the permeability of cells introduced on or near a structure without the need for direct contact between the particles and the cells. Introducing cells on a structure means that the cells are introduced so that the cells or at least a part of the cells are in contact with the structure, i.e. with the free area surface S of the structure. Introducing cells near a structure means that the cells are introduced so that the distance between the cells or at least a part of the cells and the structure is 100 μm or less, for example 50 μm, 20 μm, 10 μm, 5 μm, 3 μm, 2 μm, 1 μm, 0.5 μm or 0.1 μm. This means that the (closest) distance between the cells or at least a part of the cells and the free area surface S of the structure is 100 μm or less, for example 50 μm, 20 μm, 10 μm, 5 μm, 3 μm, 2 μm, 1 μm, 0.5 μm or 0.1 μm.
[0025] Furthermore, the method according to the invention has the advantage that no or substantially no material of the particles present in the structure is released, where substantially no material means that less than 1%, preferably less than 0.5%, less than 0.1%, less than 0.05% of the total particle mass of the particles present in the structure is released.
[0026] For the purposes of the present invention, the term "volume" (V) of a structure, also called the internal volume of the structure, is defined as the total space occupied by this structure, i.e., the total space occupied by the material and particles of the structure.
[0027] The term "free area surface" (S) of a structure is defined as the entire exterior surface of the structure that encloses the (internal) volume of the structure, i.e., all surfaces of the structure that are in direct contact with the surrounding environment. If the structure is submerged in a fluid, e.g., a liquid (a medium containing (biological) cells or a gas, e.g., air), and the structure comprises a material that is impermeable to the fluid, the free area surface of the structure can also be defined as the entire surface of the material of the structure that is in contact or may come into contact with the fluid.
[0028] Preferably, the ratio of the free area surface area S of the structure to the volume of the structure, i.e., the S / V ratio, is 10 -2 ~10 2 μm -1 range, e.g., 10 -1 ~50μm -1 , or 1 to 10 μm -1 The range is.
[0029] The shortest distance L from a particle to the free area surface S of the structure is defined as the shortest distance measured from the outer surface of the particle to the free area surface S of the structure.
[0030] The average spherical equivalent diameter d of a particle (e.g., a spherical particle, a longitudinal particle, or a particle of irregular shape) is defined as the average diameter of a sphere with an equivalent volume to that particle. The average spherical equivalent diameter d of a particle is also called the average equivalent volume diameter of the particle. If the particles consist of spherical particles, it is clear that the average spherical equivalent diameter corresponds to the average diameter of the particles.
[0031] As described above, the concentration of the particles capable of absorbing electromagnetic radiation present in the structure according to the present invention is in the range of 0.001% to 20% by volume. More preferably, the concentration of the particles capable of absorbing electromagnetic radiation present in the structure according to the present invention is in the range of 0.01% to 10% by volume or 0.01% to 5% by volume, for example, 0.05%, 0.1%, 0.2%, 0.5%, 1%, 2%, or 5% by volume.
[0032] The particles present in the structure according to the present invention are preferably embedded in the material such that the shortest distance L between at least 60% of the particles present in the structure and the free area surface S is between 1 nm and 500 nm, for example, in the range of 2 nm to 500 nm or 5 nm to 500 nm. More preferably, the particles are embedded in the material such that the shortest distance L between at least 70%, at least 80%, or at least 90% of the particles present in the structure and the free area surface S is between 1 nm and 500 nm, for example, in the range of 2 nm to 500 nm or 5 nm to 500 nm.
[0033] In a preferred embodiment, the particles are embedded in the material such that the shortest distance L between at least 60% of the particles present in the structure and the free area surface S is between 1 nm and 250 nm, for example, in the range of 2 nm to 250 nm or 5 nm to 250 nm. More preferably, the particles are embedded in the material such that the shortest distance L between at least 70% of the particles present in the structure, at least 80% of the particles present in the structure, at least 90% of the particles present in the structure and the free area surface S is between 1 nm and 250 nm, for example, in the range of 2 nm to 250 nm or 5 nm to 250 nm.
[0034] In other embodiments, the particles are embedded in the material such that the shortest distance L between at least 60% of the particles present in the structure and the free area surface S is between 1 nm and 100 nm, for example, in the range of 2 nm to 100 nm or 5 nm to 100 nm. More preferably, the particles are embedded in the material such that the shortest distance L between at least 70% of the particles present in the structure, at least 80% of the particles present in the structure, at least 90% of the particles present in the structure and the free area surface S is between 1 nm and 100 nm, for example, in the range of 2 nm to 100 nm or 5 nm to 100 nm.
[0035] Preferably, the surface density of the particles located at the shortest distance L (L is in the range of 1 nm to 500 nm) from the free area surface S of the structure is 10 -4 μm -2 ~1 / d 2 (d is the average spherical equivalent diameter of the particles in μm), for example, in the range of 2×10-4 μm -2 ~2μm -2 or 2×10 -3 μm -2 ~0.2μm -2 The surface density of particles is therefore defined as the number N of particles present in the structure multiplied by the percentage P of particles located at the shortest distance L from the free area surface S, where L is in the range of 1 nm to 500 nm, for example 5 nm to 500 nm, divided by the area of the free area surface of the structure. The surface density of particles located at a distance L in the range of 1 nm to 500 nm, for example 5 nm to 500 nm, can be calculated using the formula N x P / S.
[0036] In a preferred embodiment, the surface density of particles located at the shortest distance L from the free area surface S of the structure (L is in the range of 1 nm to 250 nm) is 10 -4 μm -2 ~1 / d 2 For example, the range is 2×10 -4 μm -2 ~2μm -2 or 2×10 -3 μm -2 ~0.2μm -2 The range is between .
[0037] In another preferred embodiment, the surface density of particles located at the shortest distance L from the free area surface S of the structure (L is in the range of 1 nm to 100 nm) is 10 -4 μm -2 ~1 / d 2 For example, the range is 2×10 -4 μm -2 ~2μm -2 or 2×10 -3 μm -2 ~0.2μm -2 The range is between .
[0038] The surface density of iron oxide particles with an average spherical equivalent diameter of 160 μm is, for example, 2 × 10 -4 μm -2 ~2μm -2 Between 1×10 -3 μm-2 ~0.4μm -2 or 2×10 -3 μm -2 ~0.2μm -2 The range is between .
[0039] In a preferred embodiment of the structure according to the invention, all or substantially all of the particles are completely embedded in the material of the structure, meaning that all or substantially all of the particles of the structure are completely surrounded by the material of the structure, so that none or substantially none of the particles are exposed on the free area surface of the structure.
[0040] For the purposes of the present invention, the term "particles exposed to the free area surface" refers to all particles that emerge from the free area surface of the structure and have at least a part of their outer surface in contact with the external environment surrounding said structure.
[0041] For purposes of the present invention, "substantially all of the particles" means at least 95% of the particles, preferably at least 99% of the particles, for example at least 99.9% of the particles.
[0042] Similarly, for purposes of the present invention, "substantially free of particles" means less than 5% particles, preferably less than 1% particles, for example less than 0.1% particles.
[0043] The particles embedded in the structures of the present invention may include any particles capable of absorbing electromagnetic radiation and adapted to produce a photothermal effect when irradiated with electromagnetic radiation.
[0044] The particles may include microparticles, nanoparticles, or a combination of microparticles and nanoparticles.
[0045] The term "microparticle" refers to a particle having a spherical equivalent diameter in the range of 1 μm to 100 μm. The term "nanoparticle" refers to a particle having a spherical equivalent diameter in the range of 1 nm to 1000 nm.
[0046] The particles can be of any shape: they can be, for example, spherical, ellipsoidal, rod-like, pyramidal, branched, or irregularly shaped.
[0047] The particles may be solid particles and may have a shell structure or a core-shell structure comprising one or more materials.
[0048] Preferred particles include metal particles, metal oxide particles, carbon or carbon-based particles, particles comprising one or more light absorbing compounds, or particles loaded or functionalized with one or more light absorbing compounds.
[0049] Examples of metal particles include gold particles, silver particles, platinum particles, palladium particles, copper particles, and alloys thereof. Preferred metal particles include gold particles, silver particles, and alloys thereof.
[0050] Examples of metal oxide particles include iron oxide, titanium oxide, zirconium oxide, cerium oxide, zinc oxide, and magnesium oxide.
[0051] Examples of carbon or carbon-based particles include graphene quantum dots, (reduced) graphene oxide, and carbon nanotubes.
[0052] Examples of particles that contain or incorporate or are functionalized with one or more light absorbing compounds include particles that contain, incorporate or are functionalized with synthetic organic or synthetic inorganic absorbers, as well as particles that contain, incorporate or are functionalized with naturally occurring absorbers or derivatives thereof. Specific examples include liposomes, solid lipid nanoparticles, polymer-based particles that contain, incorporate or are functionalized with light absorbing dye molecules such as indocyanine green, inorganic quantum dots (which have low fluorescence quantum yields), naturally occurring light absorbers such as pigments (such as melanin, rhodopsin, photopsin, or iodopsin) and synthetic analogs such as polydopamine, or photosensitizers used in photodynamic therapy.
[0053] The particles preferably comprise biocompatible particles, more preferably the particles comprise or consist of clinically approved particles.
[0054] The particles may include individual particles or combinations or clusters of two or more particles located in close proximity to one another.
[0055] Structures according to the invention may contain one type of particle or a combination of different particles, for example particles having different sizes, different compositions and / or different shapes.
[0056] Particle dimensions, for example the width, height or diameter of a particle, can be determined using transmission electron microscopy (TEM), scanning electron microscopy (SEM), or atomic force microscopy (AFM).
[0057] The size of the particles is preferably defined by the equivalent sphere diameter d (also called equivalent volume diameter).
[0058] The material of the structure in which the particles capable of absorbing electromagnetic radiation are embedded includes, for example, inorganic or inorganic-based materials, such as silica or silica-based materials or ceramic or ceramic-based materials, organic or organic-based materials, such as carbon or carbon-based materials, or polymer or polymer-based materials. The material of the structure may also include composite materials comprising at least one of the above materials, such as composite materials comprising organic and inorganic materials.
[0059] Preferred materials for the structure include or are based on polystyrene, polycaprolactone, ethylcellulose, cellulose acetophthalate, polylactic acid, polylactic-co-glycolic acid, cellulose, polyvinyl alcohol, polyethylene glycol, gelatin, collagen, silk, alginate, hyaluronic acid, dextran, starch, polycarbonate or polyacrylate.
[0060] In a preferred embodiment, the structure comprises a surface-modified material, such as a surface-modified polymeric material. Surface modification includes, for example, the application of a coating (e.g., collagen) to enhance cell adhesion to the material of the structure.
[0061] The structures may include continuous or discontinuous structures.
[0062] The structure may comprise a porous or non-porous structure. Porous structures are preferred because they have the advantage of a large free area surface and therefore a large available surface area exposed to cells introduced on or near the structure according to the method of the present invention. Preferably, the porous structure has a pore size that allows partial or complete entry of cells introduced on or near the structure into the pores. Preferably, the porous structure has a pore size that does not restrict the access of molecules present in the cell medium to the cells.
[0063] The porosity of a structure is defined as the ratio of the volume of the pores or voids of the structure to the total volume occupied by the structure, i.e., the sum of the volume V of the structure (the volume of the material and particles embedded in the material) and the volume of the pores or voids of the structure. The porosity can range from 0% to 100%. When the structure includes a porous structure, the porosity of the structure is preferably at least 50%, at least 60%, at least 80%, at least 90%, at least 95%, or at least 99%.
[0064] The structure may be flat or planar, or the structure may be non-flat, for example tubular. The surface of the structure onto which the electromagnetic radiation is irradiated may be flat or non-flat.
[0065] The structures may have smooth or non-smooth surfaces. Non-smooth surfaces include, for example, surfaces with protrusions.
[0066] The thickness of the structure is preferably in the range of 0.1 μm to 1000 μm, for example, between 0.1 μm and 100 μm, or between 1 μm and 10 μm.
[0067] The thickness of a structure is defined as the distance through the material of the structure along the shortest dimension of the structure. For example, for a flat or planar structure, the thickness corresponds to the distance of the structure measured along a direction perpendicular to the horizontal plane. For a long tubular structure, the thickness corresponds to the radial diameter of the tubular structure.
[0068] A first group of embodiments includes non-porous structures comprising a material and particles capable of absorbing electromagnetic radiation embedded in the material. Examples include polymer sheets or foils comprising particles capable of absorbing electromagnetic radiation embedded in the polymer sheets or foils.
[0069] Particularly preferred embodiments comprise or are based on polystyrene, polycaprolactone, ethylcellulose, cellulose acetophthalate, polylactic acid, polylactic-co-glycolic acid, cellulose, polyvinyl alcohol, polyethylene glycol, gelatin, collagen, silk, alginate, hyaluronic acid, dextran, starch, polycarbonate or polyacrylate.
[0070] The polymer sheet may, for example, include iron oxide particles and / or carbon particles embedded in the polymer sheet.
[0071] The first group of structures has, for example, a thickness t, a length A, and a width A'. The thickness t is preferably between 0.1 μm and 100 μm, for example, between 0.1 μm and 10 μm.
[0072] The volume V of the structure corresponds to t×A×A'.
[0073] Since the length and width of the first group of structures are usually much larger than the thickness t of the structures, the area of the free area surface of the first group of structures can be estimated to be equal to 2×A×A′. The area of the free area surface of the irradiated structure corresponds to one of the surfaces of the structure (e.g., the top or bottom), so can be estimated to be equal to A×A′.
[0074] Thus, the ratio of the area S of the free area surface of the structure to the volume V of the structure, ie the S / V ratio, corresponds to 1 / t.
[0075] A second group of embodiments includes a porous structure that includes a material and particles capable of absorbing electromagnetic radiation embedded in the material. Examples include a porous polymer structure having particles embedded in the porous polymer structure.
[0076] Examples of porous structures include structures comprising fibers (e.g., polymeric fibers), structures comprising particulates (e.g., polymeric particulates), structures comprising a combination of fibers and particulates (e.g., a combination of polymeric fibers and / or polymeric particulates), and structures comprising foams (e.g., polymeric foams). The fibers and / or particulates may be interconnected or not. Particulates, e.g., polymeric particulates, may include spherical particulates as well as irregularly shaped particulates. The particles capable of absorbing electromagnetic radiation are preferably embedded in the fibers, particulates or foams, such that the particles are preferably not (partially) exposed to the free area surface of the structure.
[0077] A first example of the second group of structures is a structure comprising (polymer) fibers. The fiber diameter of the (polymer) fibers is, for example, in the range of 0.1 μm to 10 μm, for example 0.5 μm or 1 μm. The (polymer) fibers may be interconnected or not. The (polymer) fibers may be obtained by any technique known in the art. A preferred technique for producing (polymer) fibers is electrospinning. Alternative techniques include wet spinning, melt spinning, extrusion spinning, dry spray wet spinning, emulsion spinning and suspension spinning. Preferred examples of polymers include polystyrene fibers, polycaprolactone fibers, ethyl cellulose fibers, cellulose acetophthalate fibers, polylactic acid fibers, and polylactic-co-glycolic acid based fibers. The (polymer) fibers may be surface modified.
[0078] (Polymer) fibers have a diameter d fibre The diameter and fiber length L fibre The fiber can be considered as a long cylinder with a length corresponding to the fiber volume V fibre teeth,
number
number
[0079] A second example of the second group of structures are structures comprising polymeric particulates, such as polymeric (micro)spheres. The diameter of the particulates is, for example, in the range of 0.1 μm to 10 μm, for example 0.5 μm or 1 μm. The polymeric particulates may be interconnected or not. The (polymeric) particulates may be obtained by any technique known in the art. Preferred examples of particulates include polystyrene, polycaprolactone, ethyl cellulose, cellulose acetophthalate, polylactic acid, polylactic-co-glycolic acid based fibers. The polymeric particulates may be surface modified.
[0080] The particulate matter has a diameter of d ms If the microsphere has a volume V ms teeth,
number
number
[0081] The cells are introduced onto or near the structure, for example, by applying a suspension containing the cells onto or near the structure. The cells can be introduced onto or near the structure continuously or discontinuously.
[0082] The concentration of cells in the suspension is preferably 1-10 per mL. 6 It is the range of cells.
[0083] In a preferred method, the suspension, ie, the cells, are cultured on or near the structure for a specified period of time.
[0084] In an alternative method, the cells are treated immediately or shortly after being introduced onto or near the structure by activating the structure with electromagnetic radiation.
[0085] The structure, and in particular the particles embedded in the structure, are preferably irradiated with a pulsed radiation source, although irradiation with a continuous wave radiation source is also contemplated. The structure may be irradiated with one or more pulses.
[0086] If a pulsed radiation source is used, the pulses preferably have a duration in the range of 1 fs (femtosecond) to 1 ms (millisecond), for example in the range of 1 fs to 100 μs (microseconds), in the range of 10 fs to 10 μs, in the range of 10 fs to 1 μs, or in the range of 10 fs to 10 ns.
[0087] The fluence per pulse of the radiation source (electromagnetic energy delivered per unit area) is preferably between 0.001 and 1000 J / cm 2 For example, between 0.001 and 100 J / cm 2 Between 0.01 and 10 J / cm 2 For example, between 0.1 J / cm 2 ~1J / cm 2 The range is.
[0088] The wavelength of the radiation source can range from the ultraviolet to the infrared region. In a preferred method, the wavelength range of the radiation used is from the visible to the near infrared region.
[0089] The method according to the invention shows enhanced efficiency, e.g. enhanced transfection efficiency, compared to methods known in the art, e.g. the method described in EP2272945. Although the applicant does not wish to be bound by any theory, the applicant believes that the enhanced efficiency is a direct result of the increased contact between the cells and the structure. Due to the increased contact between the cells and the structure, a larger area of the cell membrane becomes permeable, so that more and / or larger molecules can enter the cell. If the structure includes a porous structure, the efficiency can be further increased, since the free area surface is larger and the cells can reach the free area surface of the structure from various sides.
[0090] Previously, it was thought that delivery of large macromolecules into cells required high intensity laser pulses in order to create vapor nanobubbles and induce localized pressure waves that can penetrate the membrane of the cell, e.g., the plasma membrane of the cell. Surprisingly, the method according to the present invention allows the use of single laser pulses of much lower intensity, e.g., 0.001 J / cm 2 ~1J / cm 2 in the range of 0.01 J / cm 2 ~0.5J / cm 2 in the range of 0.05 J / cm 2 ~0.2J / cm 2 It has been found that it is possible to permeabilize a membrane of a cell, for example the plasma membrane of a cell, using a single laser pulse having a fluence range of 1000 nm to 1000 nm. Furthermore, the method according to the invention makes it possible to induce relatively large pores even when using low laser intensities, allowing the intracellular delivery of relatively large macromolecules, for example macromolecules with a nominal size of up to 500 kDa.
[0091] A further advantage of the method according to the invention is that fragmentation or release of particles embedded in the structure is avoided. ICP-MS analysis showed that the amount of released particle material was undetectable. This means on the one hand that the cells are not exposed to potentially toxic material of the particles, and on the other hand that the particles remain intact and functional after irradiation. In photoporation techniques known in the art, the irradiated (nano)particles are often fragmented with a single laser pulse. As a result, in techniques known in the art, the (nano)particles can often only be used once. In the method according to the invention, the structure can be repeatedly used for irradiation.
[0092] A further advantage of the method according to the invention is the ease of manufacturing the structure.
[0093] According to a second aspect of the invention, there is provided a structure suitable for use in a photothermal process for permeabilizing a cell, in particular a plasma membrane of a cell, introduced on or near the structure. The structure comprises a material and particles capable of absorbing electromagnetic radiation embedded in the material. The particles have a mean equivalent spherical diameter d. The structure defines a volume V and a free area surface S. The particles are present in the structure in a concentration ranging from 0.001% to 20% by volume (volume particles / volume structure), for example between 0.01% to 10% by volume, or ranging from 0.01% to 10% by volume. At least P percent of the particles present in the structure are located at a minimum distance L from the free area surface of the structure, L being in the range of 1 nm to 500 nm, whereby P is at least 60%.
[0094] The structure may include any of the types of structures described above.
[0095] The structures of the present invention are particularly suitable for use in drug screening, cell therapy, immunotherapy, gene therapy, cell labelling and the production of engineered cells.
[0096] The constructs are particularly suitable for use in the intracellular delivery of nucleic acids, including oligonucleotides, siRNA, mRNA, or pDNA.
[0097] The constructs are also suitable for use in intracellular delivery of nuclear proteins, including ribonucleoproteins such as Cas9 / gRNA.
[0098] Furthermore, the structures are suitable for use in the intracellular delivery of peptides and proteins, such as nanobodies or antibodies.
[0099] Additionally, the structures are suitable for use in the intracellular delivery of imaging agents such as fluorescently labeled polymers, quantum dots, iron oxide nanoparticles, gadolinium chelates, and the like.
[0100] The structures are further suitable for use in intracellular delivery of plasmonic nanoparticles for sensing and characterization purposes, such as, for example, LSPR sensors (localized surface plasmon resonance) or SERS (surface enhanced Raman spectroscopy).
[0101] The structures according to the invention are suitable for use in in vitro and ex vivo applications. The structures are further suitable for use in in vivo applications.
[0102] According to the third aspect of the present invention, there is provided the use of the structure according to the present invention, particularly in drug screening, cell therapy, immunotherapy, gene therapy, cell labeling, engineered cell manufacturing and protein interference research.The structure can be used in in vitro and ex vivo applications.The structure can also be used in in vivo applications.
[0103] In a preferred use, the construct is used in a method for increasing the permeability of a cell, as described above. [Brief description of the drawings]
[0104] The invention will now be discussed in more detail below with reference to the accompanying drawings, in which: [Figure 1]FIG. 1 is a schematic diagram showing a method for increasing cell membrane permeability according to the present invention. [Diagram 2] FIG. 13 shows calcein-AM viability staining and confocal images showing intracellular delivery of red fluorescently labeled dextran of 10 kDa (RD10) by single 7 ns laser pulses of increasing fluence. [Diagram 3] Figure 2 shows the delivery efficiency and cell viability (calcein positive cells) of red fluorescently labeled 10 kDa dextran (RD10) using different laser pulse fluences and different concentrations of iron oxide nanoparticles (IONPs). [Figure 4] Confocal images are shown of photoporation repeated first with red fluorescent 10 kDa dextran (RD10) and then with green fluorescent FITC-dextran (FD10). [Diagram 5] 1 shows flow cytometry data indicating that when photoporation was repeated with RD10 and FD10, 90% of the cells contained both RD10 and FD10. [Figure 6] Delivery efficiency is shown for sequential photoporation of HELA cells with FD10, whose concentration was doubled between each photoporation step (N=1-4). [Figure 7] Figure 2 shows the average relative mean fluorescence intensity (rMFI) per cell with increasing number of photoporation steps for sequential photoporation of HELA cells with FD10. [Figure 8] The delivery efficiency of FITC-dextran molecules of various molecular weights (10, 40, 70, 150, and 500 kD) for increasing numbers of photoporations (N=1, 2, 4) is shown. [Figure 9] The relative median fluorescence intensity (rMFI) per cell for different FITC-dextran molecules with increasing numbers of photoporations is shown. [Figure 10] Figure 1 shows the delivery efficiency and viability of FD10 in Jurkat cells for constructs containing fibers with different concentrations of IONPs and irradiated with laser pulses of different fluences. [Figure 11] Iron concentrations measured by ICP-MS are shown in untreated cells (negative control), cells incubated with IONPs (positive control), and cells treated by photoporation with structures consisting of fibers containing different concentrations of IONPs. [Figure 12] Iron concentrations measured by ICP-MS are shown in distilled water (negative control), in fibers with different concentrations of IONPs digested by aqua regia digesting amounts of fibers comparable to culture wells with different concentrations of IONPs (positive control), and in distilled water collected from the constructs after photoporation. [Figure 13] Figure 1 shows the MFI, knockdown efficiency, and cell viability of H1299 cells stably expressing GFP and grown on fiber substrates after N rounds of photoporation (N = 1-4). The fiber substrates contain IONPs with siRNA at different concentrations C (C = 0.5-50 μM). [Figure 14] Figure 1 shows intracellular delivery of FD10 in human T cells by photoporation with different IONP concentrations and laser fluences. [Figure 15] Intracellular delivery of FD10 in human T cells upon repeated photoporation (N=1-4). [Figure 16] Figure 16 shows the siRNA delivery performance in stimulated human T cells using electroporation (EP), photoporation according to the present invention (PEN), and gold nanoparticle-sensitized photoporation (PP), with Figure 16a showing the viability and Figure 16b showing the transfection yield, which is the percentage of live and transfected cells obtained by multiplying the percentage of positive cells by the percentage of live cells. [Figure 17] 1 shows an exemplary histogram depicting PD1 expression in CD3+ T cells. [Figure 18]1 shows the levels of PD1 knockdown in human CD3 T cells with siRNA up to 72 hours after delivery by electroporation (EP), photoporation according to the present invention (PEN), and gold nanoparticle-sensitized photoporation (PP). [Figure 19] 1 shows the application of constructs containing nanofibers derived from polycaprolactone (PCL) with 1% IONPs for Cas-9 gene knockout in H1299. [Figure 20] We show the application of constructs containing nanofibers derived from polycaprolactone (PCL) with 1% IONPs for macromolecule delivery in H9 human embryonic stem cells. [Figure 21] 21a and 21b show alternative examples of structures for increasing the permeability of the plasma membrane of cells comprising polymer sheets. [Figure 22] FD500 positive cells, viability, and median relative fluorescence intensity for photoporation of HeLa cells using polymer sheets with different concentrations of IONPs are shown. [Diagram 23] The percentage of FD500 positive cells, the percentage of viable cells, and the median relative fluorescence intensity for photoporation of HeLa cells with polymer sheets with a specific concentration of IONPs using different laser fluences are shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0105] The present invention will be described with respect to particular embodiments and with reference to certain drawings but the invention is not limited thereto and is illustrated only by the claims. The drawings are schematic and non-limiting. The size of some of the elements in the drawings may be exaggerated for illustrative purposes and not drawn to scale. The dimensions and relative dimensions do not correspond to actual reduction to practice of the invention.
[0106] When referring to the endpoints of a range, the values at the endpoints of the range are inclusive.
[0107] When describing the present invention, the terms used are to be construed in accordance with the following definitions, unless otherwise indicated.
[0108] Terms such as "first," "second," and the like, as used in the description and claims, are used to distinguish between similar elements and do not necessarily describe an order in time, space, ranking, or otherwise. It is to be understood that terms so used are interchangeable where appropriate, and that embodiments of the invention described herein are capable of operating in orders other than those described or illustrated herein.
[0109] The term "and / or" when referring to a list of more than one item means that any one of the listed items may be employed alone, or any combination of two or more of the listed items may be employed.
[0110] The term "cell" refers to all types of biological cells, including eukaryotic and prokaryotic cells.
[0111] The terms "increase the permeability of," "permeabilize," "permeabilizing," and "permeabilization" refer to any method that at least partially or locally changes the permeability of a membrane or barrier, such as the plasma membrane of a cell. After permeabilization, the membrane or barrier, such as the plasma membrane of a cell, is altered to be more permeable to one or more types of compounds, such as molecules, macromolecules, particles, or nanoparticles.
[0112] The terms "perforate", "perforating" or "perforation" refer to any method of providing one or more openings, holes or pores in a membrane or barrier, such as the plasma membrane of a cell. By perforating a membrane or barrier, such as the plasma membrane of a cell, an opening is created in the membrane or barrier, such as the plasma membrane of a cell, allowing the transport of a compound, such as a molecule, macromolecule, particle or nanoparticle, through the membrane or barrier, such as the plasma membrane of a cell.
[0113] For purposes of the present invention, the terms "increase the permeability of", "permeabilize", "permeabilizing" and "permeabilization" and the terms "perforate", "perforating" or "perforation" are used interchangeably.
[0114] Likewise, for purposes of the present invention, the terms "opening," "hole," and "pore" are used interchangeably. EXAMPLES
[0115] Example 1. Porous Structure Comprising a Web of Nanofibers and Particles Embedded in the Nanofibers A second embodiment of the structure according to the invention comprises a porous structure comprising nanofibers and particles capable of absorbing electromagnetic radiation embedded in the nanofibers. The example described below comprises polycaprolactone as the material of the structure and iron oxide nanopowder as the particles capable of absorbing electromagnetic radiation. It is clear that other materials and other particles can also be considered.
[0116] [1-a. Synthesis and characterization of photothermally electrospun nanofibers] The following materials are used for the synthesis of the nanofiber web: - Polycaprolactone (PCL, Mw ≈ 70,000 g / mol); - N,N-dimethylformamide (DMF); - Tetrahydrofuran (THF); - Iron oxide (Fe3O4) nanopowder (IONP) (#MKBW3262, Sigma-Aldrich, Belgium); - Poly(allylamine hydrochloride) (PAH, Mw = 17,560 g / mol, #MKBZ2824V, Sigma-Aldrich, Belgium); - concentrated sulfuric acid solution (96%) (Sigma-Aldrich); - Collagen type I rat protein (Thermo Fisher Scientific, #A1048301, Gibco™, Belgium).
[0117] IONPs were redispersed in 1:1 DMF / THF solutions supplemented with different concentrations of PCL, ranging from 0 vol% to 1.15 vol%.
[0118] The mixture thus obtained was used to produce nanofibers by electrospinning. The nanofibers were collected on a microscope glass slide (#1000912, Marienfeld, Germany) attached to a grounded rotating collector.
[0119] During electrospinning, unless otherwise stated, the applied voltage, flow rate, and electrospinning distance were fixed at 10 kV, 0.3 ml / h, and 20 cm, respectively. The grounded rotating collector was set at a rotation speed of 500 rpm. After 30 min (or the time specifically indicated), the electrospinning process was stopped and the glass slide with the nanofiber web was separated from the rotating collector and sterilized by UV irradiation for 45 min in a laminar flow cabinet.
[0120] The size and diameter of the nanofibers were determined using scanning electron microscopy. The average diameter of the fibers without IONPs was 300 nm. The inclusion of up to 1.15% by volume of IONPs did not significantly change the average diameter.
[0121] The thickness of the constructs was investigated using confocal microscopy. With increasing duration of electrospinning, the constructs gradually thickened to 4 μm after 1 h. The web did not change significantly after 30 min, so the electrospinning time was set at 30 min.
[0122] When increasing amounts of IONPs were used relative to the nanofibers, the thickness of the nanofiber web did not change significantly, clearly indicating that the thickness of the nanofiber web is independent of the IONP content within the range used.
[0123] IONPs were embedded within the nanofibers, which can be clearly seen by SEM using a voltage of 20 kV. The SEM images showed that IONPs could exist as individual particles or as clusters of two or more individual particles. For convenience, the embedded IONPs are referred to as "IONP clusters" or "clusters", and the term "IONP clusters" or clusters is interpreted to include both individual and clustered particles. SEM revealed that IONPs were embedded within the nanofibers in an area of 1000 μm2 of the SEM images. 2 It was now possible to quantify the apparent density of IONP clusters throughout the web per 1000 μm. As the IONP content increased from 0.0046 to 1.15 vol.%, the density increased from 1.7 to 192 clusters / 1000 μm. 2 increased linearly to
[0124] [1-b. Preparation of nanofiber webs as cell culture substrates] 8-well Secure-Seal™ double-sided adhesive spacers (#S24737, Invitrogen) were sterilized by UV irradiation for 45 min in a laminar flow cabinet. After removing the protective seal from one side of the adhesive spacer, it was gently attached to the nanofiber web. These samples were then immersed in distilled water for 3 min to facilitate removal of the web (with adhesive spacer on top) from the glass slide. The webs were manually cut into small pieces with one or four adhesive wells per piece (where cells can grow) and stored in PBS buffer.
[0125] These cell culture substrates were then further modified with collagen for optimal cell attachment. The cell culture substrates were immersed in a 32% sulfuric acid solution (3 ml per well of a 6-well plate) for 3 min. After washing with distilled water, they were immersed in an aqueous solution of polyelectrolyte PAH (2 mg / ml, 0.5 M NaCl) for 15 min and rinsed three times with distilled water. Due to physical adsorption of PAH on the nanofiber surface, the nanofibers became positively charged. Next, the PAH-coated nanofibers were immersed in a 0.5 mg / ml aqueous solution of type I collagen rat tail protein for 15 min and rinsed with PBS solution. Finally, the modified substrates were stored in PBS before further use.
[0126] [1-c. Cultivation or harvesting of cells on cell culture substrates for photoporation treatment] HeLa cells (#CCL-2) and Jurkat clone E6.1 (#TIB-152) were obtained from ATCC (American Type Culture Collection) and employed as models for transfection of adherent and suspension cells by photoporation. Human lung epithelial cells (H1299) stably expressing enhanced green fluorescent protein (eGFP) were used for validation of siRNA knockdown experiments. HeLa cell culture medium was made from DMEM / F-12 containing 2 mM glutamine, 100 U / mL penicillin / streptomycin and 10% heat-inactivated fetal bovine serum (FBS). H1299 and Jurkat cell culture medium consisted of RPMI1640 containing 2 mM glutamine, 100 U / mL penicillin / streptomycin and 10% FBS.
[0127] To grow adherent cells, cell culture substrates were placed in 6-well titer plates (#10062-892, VWR) supplemented with HeLa or H1299 (approximately 1 × 10 in 2 ml cell culture medium). 6 Cells were allowed to attach and grow for 24 hours in a cell incubator at 37°C in a humidified atmosphere of 5% CO2. Immediately prior to photoporation, molecules of interest that needed to be delivered to the cells were added to the cell medium.
[0128] Jurkat cells were cultured at 75 cm 2 or 175cm 2 flasks (#734-2313, #734-2315, VWR®), 5 ~1×10 6 For photoporation, the molecules of interest were added to the cell culture medium and the cells were cultured at a cell density of approximately 2 × 10 5 Cells were transferred to the cell substrate at 100 cells / well. The cells were allowed to settle on the fiber web for 5 min before starting the laser scanning for photoporation.
[0129] Final experiments were performed with human T cells obtained from Ghent University Hospital. Buffy coats were obtained from healthy donors. Peripheral blood mononuclear cells (PBMCs) were isolated by density centrifugation using Lymphoprep (Alere Technologies, Oslo, Norway). PBMCs were then incubated in IMDM (Gibco, Invitrogen, Merelbeke, Belgium) supplemented with 10% fetal calf serum (FCS, Bovogen), 100 U / ml penicillin (Gibco, Invitrogen), 100 μg / ml streptomycin (Gibco, Invitrogen), 2 mM glutamine and 5 ng / ml IL-2 (Roche, Vilvoorde, Belgium) and stimulated with CD23 / CD28 beads (Stemcell Technologies, Vancouver, Canada) at a bead to cell ratio of 1:1. After 7 days, cells (PBMCs) were harvested and re-incubated with X-ray irradiated (40 Gy) (SARRP) PBMCs (1:2 ratio) and X-ray irradiated (50 Gy) JY (5:1 ratio) feeder cells in complete IMDM supplemented with 1 μg / ml phytohemagglutinin (Remel Europe, KENT, UK). After a further 14 days, CD3+ cells were harvested and used for further experiments as indicated. Feeder cells were irradiated using a small animal radiation research platform (Xstrahl, Surrey, UK). For photoporation treatment, T cells were cultured at approximately 8 × 10 5 The cells were transferred to the culture substrate at a density of 100 cells / well with the transfection molecules already present. The cells were allowed to settle on the fiber web for 5 min before the laser treatment began.
[0130] [1-d. Photoporation of adherent cells] The method according to the present invention is shown in a schematic diagram in FIG. 1. First, a structure is provided that includes a material and particles capable of absorbing electromagnetic radiation (FIG. 1a). The structure is synthesized, for example, as described above. Subsequently, cells are grown on the structure, for example, as described above (FIG. 1b). The cells were photoporated using a custom-built optical setup previously reported with some minor modifications (RH Xiong et al., Comparison of Gold Nanoparticle Mediated Photoporation: Vapor Nanobubbles Outperform Direct Heating for Delivering Macromolecules in Live Cells, Acs Nano, 8 (2014) 6288-6296) (FIG. 1c). Briefly, a pulsed laser with a pulse duration of 7 ns was tuned at a wavelength of 647 nm (OpoletteTM HE 355 LD, OPOTEK Inc, Canada) and applied to irradiate the structure including nanofibers and IONPs. The collimated pulsed laser beam was directed through a 1° light-shaping diffuser (Physical Optics Corporation, Torrance, Canada) and combined with an achromatic lens and a 10x objective lens (Plan Fluor, Nikon) in front of the microscope entrance resulted in a laser beam width of approximately 250 μm at the sample. The laser pulse energy was monitored by an energy meter (J-25MB-HE&LE, Coherent) synchronized to the pulsed laser. To scan all cells on the structures containing nanofibers and IONPs according to the present invention (diameter approximately 9 mm), the sample was scanned through a fixed laser beam using a motorized microscope stage. The repetition rate of the laser was 20 Hz, so the scanning speed was set to 3 mm / s and the distance between subsequent lines was 0.15 mm. In this way, all cells received at least one laser pulse up to a maximum of four in the overlap area between adjacent irradiation zones.In some experiments with Jurkat or human T cells, as indicated in the text, cells were scanned multiple times. In those cases, cells were resuspended in the well and allowed to settle again between scans to allow random attachment of the cells to the nanofibers in new locations. Transfected cells are shown in Figure 1d.
[0131] [1-e. Intracellular delivery of molecules by photoporation] To evaluate the intracellular delivery of the inventive constructs by photoporation, 10 kDa red fluorescently labeled dextran (RD10) was added to HeLa cells cultured on constructs containing nanofibers and 0.23 vol% IONPs. The cells were scanned with a 7 ns pulsed laser beam (λ=647 nm) as described above. After laser treatment, the cells were washed and calcein AM viability stain was added to the cells. Examples of confocal images using different laser fluences are shown in Figure 2. Figure 2a shows a confocal image showing the green fluorescence from calcein AM viability stain, with a maximum value of 0.12 J / cm. 2 It was shown that cytotoxicity was evident only at a laser fluence of 1000 nm. Figure 2b shows confocal images showing red fluorescence from RD10, indicating increased intracellular delivery of RD10 with increasing laser fluence.
[0132] The intracellular delivery of RD10 and cell viability were systematically evaluated by confocal microscopy for various laser fluences and constructs prepared with different IONP concentrations (Figure 3). Delivery efficiency was quantified as the percentage of RD10-positive cells, and viability was expressed as the percentage of calcein-positive cells. As expected, in the absence of laser irradiation (0 J / cm 2), no significant uptake of RD10 into HeLa cells occurred. Upon laser irradiation, RD10 was successfully delivered into cells to an extent that depended on the applied laser fluence and IONP content. Increasing the laser fluence or IONP content generally resulted in greater intracellular delivery, but also gradually increased cytotoxicity. Interestingly, we found that there existed several combinations of laser fluence and IONP concentration that led to optimal delivery efficiency. For example, for constructs with the lowest IONP content of 0.023 vol.% (corresponding to 3.6 IONPs / cell), 0.56 J / cm 2 A laser fluence of 0.08 J / cm2 resulted in over 85% positive cells with a cell viability of approximately 87%, virtually identical to that obtained with constructs containing 0.23% by volume of IONPs (43 IONPs / cell), but at a laser fluence nearly seven times lower at 0.08 J / cm2. 2 It is.
[0133] [1-f. Repeated activation of constructs for cell transfection] Nanoparticle-sensitized photoporation methods known in the art use nanoparticles, e.g., gold nanoparticles, which can be activated only once due to their tendency to fragment after the first laser pulse, resulting in the loss of their photothermal function. However, multiple irradiation cycles of the structures of the present invention were evaluated with the aim of further improving the delivery efficiency.
[0134] The cells on the structures containing nanofibers and IONPs according to the present invention were irradiated twice. In the first round, RD10 was delivered as described above. The cells were then washed. Figure 4a shows a confocal image after the first round. The cells were then irradiated twice with the same structures in the presence of a 10 kDa green fluorescent FITC-dextran macromolecule (FD10). The confocal image after the second round is shown in Figure 4b. The overlay of Figure 4a and Figure 4b is shown in Figure 4c, where many cells show both green and red fluorescence.
[0135] Quantitative analysis by flow cytometry, shown in Figure 5, confirmed that 90% of the cells were positive for both RD10 and FD10.
[0136] To provide further evidence of repeated photoporation using the same constructs, HELA cells were photoporated up to four times with FD10. The FD10 concentration was doubled (0.2 mg / ml to 1.6 mg / ml) between each photoporation round to make it easier to see increased intracellular delivery (it is diffusion driven, and therefore requires a concentration gradient). The percentage of positive cells after each photoporation is shown in Figure 6. The median relative fluorescence intensity per cell after each photoporation is shown in Figure 7. While the percentage of positive cells increased from approximately 70% to approximately 90% (Figure 6), the increase in delivery was most evident from the median relative fluorescence intensity (rMFI) per cell, which increased nearly linearly with each additional round of photoporation (Figure 8).
[0137] [1-g. Intracellular delivery of macromolecules by photoporation] To evaluate the intracellular delivery of molecules with larger macromolecules, i.e., molecular weights of proteins or mRNA, 40 kDa, 70 kDa, 150 kDa, and 500 kDa FITC-dextran (FD40, FD70, FD150, and FD500) molecules were delivered into HeLa cells by 1x, 2x, and 4x photoporation. Uptake was measured by flow cytometry and expressed as the percentage of positive cells (Figure 8) and rMFI (Figure 9).
[0138] As shown in Figures 8 and 9, the delivery efficiency gradually decreased with increasing molecular weight because the molecular combinations became larger compared to the pore size, slowing molecular diffusion. Repeating the photoporation procedure generally yielded slightly more positive cells, but on average did not improve the amount delivered per cell.
[0139] From Figures 8 and 9, it can be seen that the method according to the present invention is successful in transfecting cells with compounds up to at least 500 kDa, with the percentage of transfected cells ranging from 65-90% depending on the molecular size.
[0140] [1-h. Transfection of suspension cells by photoporation] To investigate how successful the method according to the invention is for transfection of suspension cells, Jurkat cells (an immortalized line of human T lymphocytes that is widely used as a model for difficult-to-transfect primary human T cells) were used. Before adding the cells to the structure containing nanofibers and IONPs, 2 mg / ml FD10 was first added to the Jurkat cell suspension. The cells were allowed to settle for 5 min, which was enough time to collect the cells on the upper surface of the fiber web. They were then photoporated by scanning the laser beam in exactly the same way as for adherent cells. The number of available IONP clusters per cell was quantified by multiplying the area of the Jurkat cells by the IONP density (which ranged from 7.7 to 28.4 IONPs / cell in this case).
[0141] Next, we investigated transfection efficiency as a function of laser fluence and IONP content. As shown in Figures 10a, 10b, and 10c, delivery efficiency increases with increasing laser fluence at the expense of cell viability, as measured by calcein red-orange AM viability stain. Similarly, increasing the IONP content for a given laser fluence generally increases delivery efficiency. Setting a minimum viability threshold of 80%, we found that nanofibers and 0.46 vol.% IONPs (~12 IONPs / cell) and 0.16 J / cm2 achieved high transfection efficiency. 2The highest transfection efficiency (~75% positive cells) was obtained with constructs containing 0.46 vol.% IONPs and a laser fluence of 0.08 J / cm. Finally, repeated photoporation was tested (Figure 10d), and we again found that the percentage of positive cells could be increased by repeating the procedure with little effect on cell viability. For the above experiments, we used a 0.46 vol.% IONPs containing nanofibers and a laser fluence of 0.08 J / cm, which was suboptimal. 2 Note that the stepwise improvement is better illustrated using a 3D laser scan of the nanofibers. Between subsequent laser scans, the cells were gently resuspended and allowed to settle again to allow the cells to randomly attach to the nanofibers at their new locations.
[0142] [1-i. ICP-MS measurements to detect possible leakage of IONPs from nanofibers and IONP-containing structures upon laser irradiation] To assess whether the cells were in direct contact with particles capable of absorbing electromagnetic radiation embedded in the material of the construct, the iron content of the cells after photoporation was measured by ICP-MS (Inductively Coupled Plasma Mass Spectrometry).
[0143] Irradiation of the nanofibers and IONP-containing structures was performed with and without the presence of cells on the fibers. When cells were not present, distilled water was added to the nanofibers and particle-containing structures. After laser treatment for ICP-MS analysis, the distilled water was collected again. Samples containing cells were prepared as described above. After laser irradiation, cells were collected by washing with PBS for suspension cells or by trypsinization for adherent cells. Finally, 100 μl of aqua regia (a 3:1 mixture of hydrochloric and nitric acids) was added to the samples to decompose cells or other organic matter that may be present. The iron content was then measured by ICP-MS (Agilent 8800, Santa Clara, CA, USA). Specifically, the sample solution was diluted 100-fold in a metal-free tube, Y was added as an internal standard (final concentration 1 μg / L) to correct for instrument instability and / or signal drift, and brought to a final volume of 10 mL with 2% HNO3. External calibration standards (0, 0.5, 1, 2.5, 5, and 10 μg / L Fe + 1 μg / LY) were prepared from the 1,000 mg / L Fe standard stock solution by diluting to the appropriate volume using a weak acidic solution, thus mimicking the matrix of the sample solutions. Throughout all steps of sample preparation, the solutions were thoroughly mixed using a vortex mixer.
[0144] Internal standard correction was performed according to the following formula:
number
[0145] [1-j. Efficient gene silencing in adherent cells by photoporation] To evaluate the intracellular delivery of siRNA as a functional polymer, anti-eGFP siRNA was delivered into adherent H1299 cells stably expressing green fluorescent protein (GFP). Cells were grown on collagen-coated nanofiber webs with 0.23 vol.% IONPs for 24 h at 37 °C and then photoporated with control and anti-GFP siRNA (0.08 J / cm). 2) and allowed to grow for 24 h before measuring GFP expression. Examination by confocal microscopy of trial experiments with 5 μM siRNA showed a clear GFP expression reduction when treated with anti-GFP siRNA but not with control siRNA. Confirming these results with flow cytometry, GFP-positive cells were 77% when treated with control siRNA, but reduced to 28% when treated with functional siRNA. We systematically evaluated knockdown efficiency and cytotoxicity as a function of siRNA concentration (0.5, 1, 2, 5 μM). eGFP expression decreased with increasing siRNA concentration, reaching 75% of cells with significant gene silencing at 5 μM siRNA (Figure 13a, Figure 13b). We evaluated whether repeated photoporation was also beneficial for siRNA gene silencing. Indeed, eGFP expression gradually decreased with repeated laser scanning up to four times for each scan, and knockdown efficiency reached up to 75% after four repeated laser irradiations. In all conditions, cell viability, as measured here by the cell Titer-Glo luminescent assay, remained very good (>75%, FIG. 13b).
[0146] [12-k.Efficient gene silencing in primary human T cells by photoporation] Photoporation of CD3+ T cells from human patients on constructs containing nanofibers and IONPs according to the present invention was evaluated. Constructs with 0.23 vol%, 1.15 vol%, and 2.3 vol% IONPs were prepared and T cells were photoporated at 0.16 J / cm. 2 The cells were transfected at a fixed laser fluence of 1.15 J / cm (as this was optimal for Jurkat). The best transfection efficiency (approximately 30% positive cells) was obtained with 1.15% by volume of IONPs (Figure 14). The laser fluence was then optimized, and a transfection efficiency of 0.16 J / cm was obtained. 2 Interestingly, the laser fluence was optimized at 0.32 J / cm 2Increasing the photoporation current to I=0.16 J / cm did not result in further improvements in transfection efficiency as predicted by theoretical simulations. Similar to Jurkat, repeated photoporation improved the percentage of FD10-positive cells (Figure 15). For example, three photoporations achieved a transfection efficiency of 53%, with cell viability exceeding 60%. Based on these results, we chose to use I=0.16 J / cm for further experiments with human T cells. 2 , 1.15 vol% IONP neutral nanofibers, and N=3 were selected.
[0147] The siRNA delivery performance of photoporation in stimulated human T cells was tested using a fluorescently labeled model siRNA (without biological function). A direct comparison was performed with two other established physical transfection techniques: electroporation and conventional gold nanoparticle-sensitized photoporation. In Figure 16, electroporation is EP, photoporation according to the present invention is PEN, and gold nanoparticle-sensitized photoporation is PP. As is frequently observed with electroporation, very few cells survived the treatment (14.2%, Figure 16b), but almost all were positive for siRNA (94.2%, Figure 16a). The product of both measurements is the so-called transfection yield, i.e. the percentage of cells that were both alive and transfected, which reached only 13.5% with electroporation. Both gold nanoparticle-sensitized photoporation and photoporation using the structure according to the present invention were much gentler on the cells, with cell viability exceeding 60% and positive cells at 40-50%. This resulted in a transfection yield of 35% for photoporation using the constructs of the present invention and 30% for gold nanoparticle-sensitized photoporation (Figure 16b). It can therefore be concluded that the transfection yield using the photoporation method of the present invention is similar to that of conventional photoporation, but more than 2.5 times better than electroporation. The latter is a surprising achievement considering the fact that this result is obtained without any direct contact between the particles of the present invention and the cells.
[0148] To evaluate gene silencing by functional siRNA, the PD-1 receptor was targeted. On the first day, T cells were collected from donors and subjected to the first round of stimulation. After 7 days, cells were collected for siRNA transfection and subjected to the second round of stimulation. Cells were transfected with 1 μM siPD1, and PD1 expression was quantified after 24, 48, and 72 hours by flow cytometry after PD-1 antibody staining. Transfection was again compared between electroporation, photoporation, and gold nanoparticle-sensitized photoporation. Exemplary flow cytometry histograms are shown in FIG. 17, where k shows cells 48 hours after photoporation with control siRNA and siPD1, with the latter showing a decrease in PD1 expression. Knockdown efficiency was quantified over time from the decrease in PD-1 antibody staining across the entire population of live cells (FIG. 18). All three transfection methods yielded similar levels of PD-1 gene silencing, reaching a maximum of 40% knockdown after 48 hours. Keeping in mind that photoporation exhibits a 2.5-fold higher transfection yield than electroporation due to its low toxicity, we confirm that photoporation is a very promising and effective transfection method to produce engineered T cells for adoptive T cell therapy.
[0149] Figure 19 shows the application of structures containing nanofibers derived from polycaprolactone (PCL) with 1% IONPs for Cas-9 gene knockout in H1299. Figure 19a shows confocal images showing the green fluorescence of H1299 cells stably expressing GFP before (left) and after (right) photoporation with 4 μM Cas-9 ribonucleoprotein designed to knockout GFP expression. Samples were photoinduced with 0.08 J / cm 2The cells were scanned once with a laser fluence of 0.5 μM. Figure 19b shows the corresponding cytometric histograms illustrating how eGFP expression is distributed throughout the cell population before and after photoporation with 90.5% and 33.5% eGFP positive cells, respectively. Figures 19c and 19d show the median fluorescence intensity (MFI) and knockdown efficiency (= percentage of eGFP negative cells), respectively, of H1299 cells photoporated with increasing concentrations of Cas-9 ribonucleoprotein (0.5, 1, 2, 4 μM) and multiple times (N=2, 3, 4) at a concentration of 0.5 μM.
[0150] We show the application of constructs containing nanofibers derived from polycaprolactone (PCL) with 1% IONPs for macromolecule delivery in H9 human embryonic stem cells.
[0151] Figure 20a shows confocal images demonstrating successful delivery of 10 kDa (RD10) fluorescently labeled dextran before photoporation (top row), after one photoporation cycle (second row), and after two photoporation cycles (bottom row). Live cells were stained with calcein AM, and dead cells can be recognized by a positive signal for propidium iodide (PI). Photoporation was performed at 0.08 J / cm 2 The experiment was carried out using a laser fluence of 100 Hz.
[0152] Figure 20b shows the laser fluence (I = 0.08, 0.12, 0.24 J / cm 2 ) and multiple photoporation cycles (N=2, 3, 4), as a function of cell viability and percentage of RD-positive cells, quantified by image processing.
[0153] Example 2: Non-porous structure containing polymeric material and nanoparticles Figure 21a shows a schematic diagram of an embodiment of a structure 1 according to the present invention. Figure 21b shows a cross-sectional view of the structure 1 shown in Figure 21a along the line A-A'. The structure 1 comprises a polymer sheet comprising a polymer material 2 and particles 3 capable of absorbing electromagnetic radiation. The particles 3 comprise, for example, carbon particles or iron oxide particles, or a combination of carbon particles and iron oxide particles. The particles 3 are embedded in the material 2 and have, for example, a mean equivalent spherical diameter d of 1000 nm.
[0154] The thickness t of the structure is in the range of 0.1 μm to 100 μm, for example, 1 μm, 2 μm or 5 μm.
[0155] The ratio of the area S of the free area surface of the structure to the volume V of the structure, ie the S / V ratio, corresponds to 1 / t.
[0156] The polymer sheet preferably comprises or is based on polystyrene, polycaprolactone, ethylcellulose, cellulose acetophthalate or polylactic-co-glycolic acid, cellulose, polyvinyl alcohol, polyethylene glycol, gelatin, collagen, silk, alginate, hyaluronic acid, dextran, starch, polycarbonate or polyacrylate.
[0157] The particles are present in the material at a concentration ranging from 0.001% to 20% by volume (volume particles / volume structure), for example at a concentration of 1%, 2% or 5% by volume.
[0158] Preferably, all or substantially all of the particles are completely embedded in the material of the structure, meaning that all of the structure or substantially all of the particles of the structure are completely surrounded by the material of the structure and not all particles or substantially all particles are exposed to the free area surface of the structure.
[0159] At least 60% of the particles present in the structure are embedded in the material such that the shortest distance L between the particle and the free area surface S is in the range of 1 nm to 100 nm.
[0160] FIG. 22 shows the percentage of FD500 (FICT-Dextran 500 kDa) positive cells, cell viability as measured by Cell Titer-Glo metabolic assay, and median relative fluorescence intensity for photoporation of HeLa cells using PLA films without IONP (2% PLA) (control), PLA films with 0.005% IONP (2% PLA), PLA films with 0.01% IONP (2% PLA), and PLA films with 0.1% IONP (2% PLA).
[0161] In addition, the percentage of FD500 positive cells, viability, and median relative fluorescence intensity (rMFI) were determined using a 100-μL ELISA kit (100 μg / mL, 0.3 J / cm 2 ). 2 (=E1), 0.5 J / cm 2 (=E2), 0.84 J / cm 2 (=E3), 1.26 J / cm 2 (=E4), and 1.6 J / cm 2 Photoporation of HeLa cells using PLA film with 0.025% IONP (2% PLA) was determined using different laser fluences of (=E5) and (1 photoporation cycle). The results are shown in FIG.
Claims
1. 1. A method for increasing the permeability of the plasma membrane of a cell, comprising: providing a porous or non-porous structure comprising a material and particles embedded in the material, the particles having a mean equivalent spherical diameter d capable of absorbing electromagnetic radiation, the structure defining a volume V and a free area surface S, the particles being present in the structure at a concentration in the range of 0.001% to 20% by volume (volume particles / volume structure), at least P percent of the particles present in the structure being embedded in the material such that a shortest distance L between the P percent of the particles and the free area surface S of the structure is in the range of 1 nm to 500 nm, and P is at least 60 percent; introducing at least one cell onto said structure or at a distance of less than 100 μm from said structure; and exposing the structure to electromagnetic radiation; the particles comprise particles selected from the group consisting of metal particles, metal oxide particles, carbon or carbon-based particles, and particles comprising one or more light absorbing compounds, and particles incorporating or functionalized with one or more light absorbing compounds; and The method of claim 1, wherein the material comprises an inorganic or inorganic-based material, a ceramic or ceramic-based material, an organic or organic-based material, or a composite comprising at least one of said materials, or the material is selected from the group consisting of polystyrene, polycaprolactone, ethyl cellulose, cellulose acetophthalate, polylactic acid, polylactic-co-glycolic acid, cellulose, polyvinyl alcohol, polyethylene glycol, gelatin, collagen, silk, alginate, hyaluronic acid, dextran, starch, polycarbonate, and polyacrylate.
2. The method of claim 1 , wherein the particles are present in the structure at a concentration ranging from 0.01% to 5% by volume.
3. The surface density of particles located at a minimum distance L from the free area surface S of the structure (L is in the range of 5 nm to 500 nm) is 10 ‐4 μm ‐2 ~1 / d 2 3. The method of claim 1 or 2, wherein the surface density of the particles is defined as the number N of particles present in the structure multiplied by the percentage P of the particles located at the shortest distance L from the free area surface S divided by the area of the free area surface of the structure (N x P / S).
4. The method of any one of claims 1 to 3, wherein at least 95% of the particles are not exposed at the free area surface of the structure.
5. The method of any one of claims 1 to 4, wherein the structure comprises a porous structure having a porosity of at least 50%.
6. The method of claim 5 , wherein the porous structure comprises fibers, particulate matter, a combination of fibers and particulate matter, or a foam, and the particles are embedded in the fibers, the particulate matter, or the foam.
7. The irradiation has pulses with durations in the range of 1 fs to 1 μs and / or has a radiation intensity of 0.001 to 10 J / cm 2 The method of any one of claims 1 to 6, comprising irradiation with a pulsed radiation source having a fluence per pulse in the range of
8. 1. A porous structure suitable for use in a photothermal process for permeabilizing cells introduced on or near the structure, comprising a material selected from fibers, particulate matter, a combination of fibers and particulate matter, or a foam, and particles embedded in the material, the particles having a mean equivalent spherical diameter d capable of absorbing electromagnetic radiation, and defining a volume V and a free area surface S, the particles being present in the structure at a concentration in the range of 0.001% to 20% by volume (volume particles / volume structure), at least 60 percent of the particles present in the structure being embedded in the material such that the shortest distance L between the at least 60 percent of the particles and the free area surface S of the structure is in the range of 1 nm to 500 nm, the particles are selected from the group consisting of metal particles, metal oxide particles, carbon or carbon-based particles, and particles comprising one or more light absorbing compounds, and particles incorporating or functionalized with one or more light absorbing compounds; and A structure, wherein the cells are less than 100 μm away from the porous structure.
9. 1. A non-porous structure suitable for use in a photothermal process for permeabilizing cells introduced onto or near the structure, comprising: the non-porous structure comprises a polymer sheet or foil and includes particles capable of absorbing electromagnetic radiation embedded in the polymer sheet or foil, the particles having an average equivalent spherical diameter d, the structure defining a volume V and a free area surface S, the particles being present within the non-porous structure at a concentration ranging from 0.001% to 20% by volume (volume particles / volume structure); At least 60% of the particles present in the non-porous structure The shortest distance L between at least 60 percent of the particles and the free area surface S of the non-porous structure is in the range of 1 nm to 500 nm. embedded in said polymer sheet or foil, such that the particles comprise particles selected from the group consisting of metal particles, metal oxide particles, carbon or carbon-based particles, and particles comprising one or more light absorbing compounds, and particles incorporating or functionalized with one or more light absorbing compounds; and A structure, wherein the cells are less than 100 μm away from the non-porous structure.
Citation Information
Patent Citations
Nanoparticles - external field effects
WO2010012816A1
Methods for preparing and orientating biopolymer nanofibres and a composite material comprising the same
WO2016050357A1